Perbandingan Harga Pokok Produksi Metode Full Costing dan Metode Konvensional Pada Bakso H. Lili - Diandra Meivita Hanum; Devina Fara Rafifah; Dini Amalia Putri; Amanda Nuranini Solikhatin; Tiar Lina Situngkir (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the inconsistent cost calculations and unclear cost classifications found in UMKM Bakso H. Lili, which have created pricing decisions that are not fully aligned with actual production conditions. The research aims to compare the full costing and traditional costing methods, clarify the distinction between fixed and variable costs, and provide a more reliable basis for determining production costs. A descriptive quantitative case study approach was applied, using data collected through semi-structured interviews and documentation of production expenditures. The analysis involved classifying cost components and calculating production costs under both methods. The full costing method resulted in a total production cost of Rp186,599,192, while the traditional method produced Rp183,934,500. Unit costs were Rp10,663 and Rp10,511, respectively. The difference arises from the exclusion of fixed manufacturing overhead in the traditional method, indicating that full costing offers a more complete representation of actual costs. These findings suggest that adopting the full costing method provides more accurate cost information for setting realistic selling prices and improving managerial decision-making within UMKM Bakso H. Lili.